The challenges of implementing a multi-sectoral approach through Aids Councils in the Eastern Cape Province - Palmer, Eurica (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--Stellenbosch University, 2008.